Effective Learning for Early Childhood during Global Pandemic - Mohammad Fauziddin; Diana Mayasari; Lussy Midani Rizki (AL-ISHLAH: Jurnal Pendidikan, 2021)
Several previous research studies stated that parents have a big role in implementing learning during a global pandemic, which is well-known with COVID-19. This research aims to review the role and strategies of parents in assisting children to learn during the pandemic. The research method is a literature study by selecting various articles of research results according to the research study. The results of the study indicate that effective learning can be done by recognizing children's learning styles, creating a positive environment, creating various learning methods with teacher coordination. In addition to parents, the government and teachers also have a stake in the success of practical learning in achieving learning goals: online learning through instructional videos, assignments tailored to learning conditions at home, and preparing learning tools to be carried out at home. These findings provide valuable insights for parents to be alert and more creative in creating effective learning.